The evolution of acute stroke care in Germany from 2019 to 2021: analysis of nation-wide administrative datasets - Ungerer, Matthias; Bartig, Dirk; Richter, Daniel; Krogias, Christos; Hacke, Werner; Gumbinger, Christoph (Neurological research and practice, 2024)
BACKGROUND: The treatment of ischemic stroke (IS) has changed considerably in recent years. Particularly the advent of mechanical thrombectomy (MTE) has revolutionized the available treatment options. Most patients in developed countries have access to intravenous thrombolysis (IVT). However access to MTE remains restricted in some regions despite efforts to increase its availability. We performed an evaluation of national datasets to monitor improvements made in access to revascularization therapies for IS patients in Germany. METHODS: We analyzed national datasets on German Diagnosis-Related Groups and structured quality reports by extracting information of patients admitted with stroke with and without IVT and MTE for the period of 2019-2021. Data from 2016 and limited data for 2022 were also included for comparison. RESULTS: Admissions with ischemic stroke declined during the years of the COVID 19 pandemic by 4.5% from 227,258 in 2019 to 216,923 in 2021. IVT rates were stable with 16.3% being treated with IVT in 2019 and 2021. MTE rates continued to increase from 7.1 to 8.4% and the number of MTE centers increased by 14.8% in the same period. Over 87.3% of MTEs were performed in centers with a case volume exceeding 50 cases per year in 2021. The largest increase in the relative share of MTEs was seen in large MTE centers (n ≥ 200). Patient age for MTEs surpassed the age for IVTs in 2019 and the proportion of patients ≥ 80 years receiving MTE continued to increase. The proportion of regions in Germany with poor MTE rates (≤ 4.1%) decreased significantly from 2019 (12.3%) to 2021 (5.3%) (p < 0.001). CONCLUSIONS: We found strong evidence that while IVT rates reached a temporary ceiling effect, both the absolute number of and access to MTEs continued to increase in Germany. Regional disparities have become less significant and the majority of MTEs are performed in centers with medium or high case volumes.
Gesehen am 09.02.2024